PENGARUH STRUKTUR MODAL, PROFITABILITAS TERHADAP DETERMINASI MANAJEMEN LABA DAN STRATEGI DIVERSIFIKASI - Dayani Okvi Yanto; Lela Nurlaela Wati (STIE Muhammadiyah Jakarta, 2020)
This study aims to examine the effect of capital structure on earnings management, profitability on earnings management and diversification strategies to moderate the effect of capital structure on earnings management. This study uses data from 93 manufacturing companies listed on the Stock Exchange Index (IDX) during the period 2014 to 2018 using Moderating Regression Analysis (MRA). The results showed that capital structure had no effect on earnings management. Profitability with the ROA proxy has a significant positive effect on earnings management, but the diversification strategy is not able to moderate the relationship of capital structure to earnings management. Profitability can build earnings management actions by way of income minimizaation and income maximization, because with good performance through the level of profitability, investors will be interested in investing the capital.